Global floods and water availability driven by atmospheric rivers - Paltan, H; Waliser, D; Lim, W; Guan, B; Yamazaki, D; Pant, R; Dadson, S (American Geophysical Union, 2017)
Whilst emerging regional evidence shows that atmospheric rivers (ARs) can exert strong impacts on local water availability and flooding, their role in shaping global hydrological extremes has not yet been investigated. Here we quantify the relative contribution of ARs variability to both flood hazard and water availability. We find that globally, precipitation from ARs contributes 22% of total global runoff, with a number of regions reaching 50% or more. In areas where their influence is strongest, ARs may increase the occurrence of floods by 80%, whilst absence of ARs may increase the occurrence of hydrological droughts events by up to 90%. We also find that ~300 million people are exposed to additional floods and droughts due the occurrence of ARs. ARs provide a source of hydro-climatic variability whose beneficial or damaging effects depend on the capacity of water resources managers to predict and adapt to them.